Editorial: Health (in)equity - examinations of the role of culture and trust - Stefanovska-Petkovska, M.; Alarcão, V. (Frontiers in Public Health, 2022)
Our health throughout the life course is a peculiar, individualized interaction of nature and nurture. Achievements in science have provided an improved understanding of the role of genetics and environment contribute to disease and disability, and biomedical interventions have often been able to provide the prospect of bringing a person back to full health or living with the disease with reduced discomfort. Nevertheless, how sociocultural behaviors and environmental factors (nurture) can trigger biological and genetic processes (nature), not just the other way around, has been largely neglected (1–4).